(untitled) (Baghdad Science Journal, 2011)
This work describes the effect of temperature on the phase transformation of titanium dioxide (TiO2) prepared using metal organic precursors as starting materials. X-ray diffraction (XRD) was used to investigate the structural properties of TiO2 gels calcined at different temperatures (300, 500, 700) ?C. the results showed that the samples have typical peaks of TiO2 polycrystalline brookite nanopowders after calcined at (300 ?C), which confirmed by (111), (121), (200), (012), (131), (220), (040), (231), (132) and (232) diffraction peaks. Also, XRD diffraction spectra showed the presence of crystallites of anatase with low proportion of rutile phase where calcined at (500 ?C), while rutile phase domains at (700 ?C). The crystallite size of TiO2 nanopowders was calculated by Scherer’s formula and showed that the crystallite size decreased and then increased with increasing the annealing temperature.